Effects of Recombinant Human Granulocyte Colony-Stimulating Factor (Filgrastim) on ECG Parameters in Neutropenic Patients A Single-Centre, Prospective Study - DENİZBAŞI ALTINOK, ARZU; ONUR, ÖZGE ECMEL (ADIS INT LTD, 2009)
Background and objective: Human granulocyte colony-stimulating factor (G-CSF) is a haematopoietic hormone that promotes the growth, proliferation, differentiation and maturation of neutrophil precursors. Filgrastim is a recombinant human G-CSF. Myocardial infarction, atrial fibrillation and arrhythmia have been reported in several patients with malignancy receiving filgrastim, but a causal relationship with the drug has not been established. The purpose of this study was to investigate the changes in ECG parameters in neutropenic patients during treatment with filgrastim. Methods: This was a single-centre, prospective study carried out in a hospital emergency room. Patients with neutropenia and malignancy who were required to receive filgrastim were eligible for the study. After a reference ECG had been obtained, filgrastim was administered to all patients at a dose of 5 mu g/kg/day subcutaneously for 2 days. Follow-up ECGs were then obtained at 12-hourly intervals. Continuous telemetric monitoring was conducted throughout hospitalization. Results: Serial ECG parameters were compared in 102 patients. There were no statistically significant differences between baseline and follow-up ECG measurements of rhythm, P-wave duration, PR interval, QRS-wave duration, corrected QT (QTc) interval, ECG axis, premature supraventricular events, ventricular arrhythmia, R-wave progression, right bundle branch block or left bundle branch block. There was a significant reduction in mean heart rate in subsequent ECGs compared with baseline (p < 0.05). Conclusion: This study did not demonstrate any ECG changes other than a significant reduction in mean heart rate in this selected population of neutropenic patients given 2 days' treatment with subcutaneous 5 mu g/kg/day of filgrastim.
Keywords: CHEMOTHERAPY; COMPLICATIONS; CANCER